PREVALENCE AND CHARACTERISTICS OF MULTIDRUG-RESISTANT ACINETOBACTER BAUMANNII CASES AT THE DR.WAHIDIN SUDIROHUSODO GENERAL HOSPITAL IN MAKASSAR - Dewi Kartika Tungadi; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Multidrug-resistant Acinetobacter baumannii (MDRAB) is a strain that is resistant to three or more classes of antibiotics. As the prevalence of MDRAB increases, the antibiotics of choice become limited. Identification of MDRAB is required to manage and control infection. This research was conducted to determine the prevalence and characteristics of MDRAB in the Wahidin Sudirohusodo Hospital Makassar. This research was a retrospective study, conducted from January to December 2016. Bacterial identification and antimicrobial susceptibility testing (AST) were performed using VITEK 2. The patient data were obtained from the medical records. A total of 323 Acinetobacter baumannii isolates was obtained, consisting of 188 isolates in January-June 2016 and 36 of which were MDRAB (19.15%) with the average length-of-stay 33 days; and 135 isolates in July-December 2016 and 31 of which were MDRAB (22.96%) with the average length-of-stay 27 days. Multidrug-resistant Acinetobacter baumannii was mostly discovered from patients using three or more medical devices and on a single antibiotic therapy. Multidrug-resistant Acinetobacter baumannii isolates were mostly obtained from sputum and pus specimens, and the majority of patients had an infection and respiratory diseases. The most comorbid diseases in MDRAB were endocrine-metabolic diseases. The result of AST showed 100% and 96% susceptibility to Polymyxin B; 71.43% and 54.84% to Amikacin; 66.67% and 50% to Trimethoprim/Sulfamethoxazole, respectively. Prevalence of MDRAB in 2016 increased from January-June (19.15%) to July-December (22.96%), suggesting a need to identify patients at risk for MDRAB infection and to promote the rational use of antibiotics. Polymyxin B, Amikacin, and Trimethoprim/Sulfamethoxazole are the antibiotics of choice to treat MDRAB.